2009
DOI: 10.1160/th09-03-0156
|View full text |Cite
|
Sign up to set email alerts
|

α1-acid glycoprotein (AGP)-induced platelet shape change involves the Rho/Rho kinase signalling pathway

Abstract: alpha(1)-acid glycoprotein (AGP) is an acute-phase protein that contributes to inflammation processes. The role of AGP in platelet activation and thrombosis is, however, largely unknown. Therefore, we thoroughly investigated the effects of AGP on human platelets. Platelets were isolated from healthy volunteers and subsequently exposed to AGP. Platelet responses were monitored as change in light transmission, intracellular calcium concentration, light microscopy and protein phosphorylation by Western blot. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Rho activation and minimal Ca 2+ mobilization) is not linked to formation of platelet aggregates. Interestingly, we recently showed that the acute-phase reactant alpha1-acid glycoprotein caused platelet shape change, but not secretion or aggregation, via activation of the same intracellular signaling pathways [31]. This may imply that acute inflammation is associated with priming of platelets via molecules such as PR3 and alpha1-acid glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Rho activation and minimal Ca 2+ mobilization) is not linked to formation of platelet aggregates. Interestingly, we recently showed that the acute-phase reactant alpha1-acid glycoprotein caused platelet shape change, but not secretion or aggregation, via activation of the same intracellular signaling pathways [31]. This may imply that acute inflammation is associated with priming of platelets via molecules such as PR3 and alpha1-acid glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a case report of angiography verified coronary thrombosis induced by intracoronary acetylcholine injection [38]. Experimentally, some of the OP (soman and paraoxon) poisonings involved increase synthesis of Alpha (1)-acid glycoprothein [39] which induced platelet shape change and activation, indicating the influence of OPs on hemostasis and thrombosis using this mechanism [40]. The ACh induced prothrombotic effects were potentiated in the atherosclerotic vessels [41], giving the potential to OP poisoning to increase the prorthrombotic activity and pulmonary vasoconstrictive tone in patients with comorbidities, as it was the case with our patient with a history of HTA and hyperlypidemia.…”
Section: Discussionmentioning
confidence: 99%
“…33 Ischemic stroke is a heterogeneous disease. 34,35 Large artery atherosclerosis, such as carotid plaque, is an established risk factor for cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%